2022
DOI: 10.1111/josi.12551
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational contact during and beyond COVID‐19

Abstract: Intergenerational contact is crucial for promoting intergenerational harmony and reducing ageism. However, the COVID‐19 pandemic has disrupted and changed the nature and frequency of intergenerational contact. In addition, research suggests that both ageism towards older adults and intergenerational threat regarding succession and consumption, have increased. Through the lens of the Temporally Integrated Model of Intergroup Contact and Threat (TIMICAT; Abrams & Eller, 2016), we explore the implications of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 123 publications
0
27
0
Order By: Relevance
“…This, in turn, impacted people's well-being, increased the risk of suicidal behaviour (see Hafford-Letchfield et al, 2022), and increased risk of financial crisis (see also Lytle & Levy, 2022;McDarby, 2022;Drury et al, 2022;Kanik et al, 2022;Spaccatini et al, 2022). Whilst some studies reported that participants maintained their social contacts, others mentioned the quantity and quality of social contacts deteriorated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, impacted people's well-being, increased the risk of suicidal behaviour (see Hafford-Letchfield et al, 2022), and increased risk of financial crisis (see also Lytle & Levy, 2022;McDarby, 2022;Drury et al, 2022;Kanik et al, 2022;Spaccatini et al, 2022). Whilst some studies reported that participants maintained their social contacts, others mentioned the quantity and quality of social contacts deteriorated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research highlights that the COVID-19 health and safety measures have led to increased mental health problems, such as increased feelings of depression, anxiety, social isolation, and loneliness, potentially cognitive decline (Allen et al 2021;Bailey et al, 2021;Dahlberg, 2021;Derrer-Merk et al, 2022b;Derrer-Merk et al, 2022a;Heidinger & Richter, 2020;Richter & Heidinger, 2021;Krendl & Perry, 2021;Litwin & Levinsky, 2021;De Pue et al 2021;Shahid et al, 2020;Smith et al, 2020;Cohn-Schwartz et al, 2022;Tsoukalis-Chaikalis et al, 2021;van Gerwen et al, 2021;Victor et al, 2022;Vrach &Tomar, 2020). Other studies reported the consequences of age discrimination (Derrer-Merk et al, 2022c;Lytle & Levy, 2022;MCDarby, 2022;Drury et al, 2022;Kanik et al, 2022;Spaccatini et al, 2022;Sutter et al, 2022;Swift & Chasteen, 2021;). Risk communication and how it is perceived by society are also important aspects of risk management in a pandemic such as COVID-19 (Sandman, 2003(Sandman, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy is to promote solidarity among different generations. In this regard, research has provided abundant evidence that interventions based on education as well as contact between different age groups are effective in reducing ageist attitudes and behaviors (Burnes et al, 2019;Drury et al, 2022). In this regard, it should be also important to emphasize in media and public discourses the social value of the numerous episodes of intergenerational solidarity emerged during the pandemic, with younger people helping older ones in doing the grocery shopping and maintaining social connections with others (Ayalon et al, 2020;Silva et al, 2021).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Research from multiple disciplines clearly demonstrated that the COVID‐19 pandemic has exacerbated prejudice towards older population (Fraser et al., 2020; analysis of tweets in the English language in Jimenez‐Sotomayor et al., 2020; Ng et al., 2021; Ng et al., 2022; review of international literature in Silva et al., 2021; Swift & Chasteen, 2021) with negative consequences for their wellbeing (Cohn‐Schwartz et al., 2022; Derrer‐Merk et al., 2022). Ng et al.…”
Section: Introductionmentioning
confidence: 99%
“…Ehni and Wahl (2020) in Germany, developed a series of propositions about how to fight ageism during the pandemic. These were: it is important to recognize the heterogeneity of older adults; age limits of medical support are unethical; mass deficit views of old age are dangerous; intergenerational solidarity must be supported; paternalistic assumptions must be resisted; the use of new technology among older adults should be fostered; and finally, knowledge of gerontology should inform policymaking (see also in this issue Lytle & Levy, 2022; Drury et al., 2022; Jarrott et al., 2022; Ng et al., 2022; Sutter et al., 2022). In addition, attention has been drawn to digital exclusion (Sourbati & Behrendt, 2020; Rosales & Fernández‐Ardèvol, 2020) and enforced isolation (Fletcher, 2021) as forms of ageism.…”
Section: Introductionmentioning
confidence: 99%